ROLE OF EXTERNAL STAKEHOLDERS IN TOURISM DEVELOPMENT AND COMMUNITY EMPOWERMENT - Eva Rachmawati; Joanna Fountain (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: This paper explores the external stakeholder role in empowering the local community in tourism development. The objectives are examined through Namo Sialang village communities, a case study that purposefully selected to represent communities where tourism was developed in a bottom-up approach, which is a good start for community empowerment Research methods: The approach used is an in-depth interview with stakeholders that involved in tourism development in the village. Results and discussions: The finding indicated that stakeholder activities more likely to create ‘power over' within the community, which is an unexpected outcome for community empowerment. It is because their activities are focused only on certain community group (e.g., tourism industry member, tourism organization member) and have not considered the wider community. The material was given also more likely focused on tourist needs, and not for what community needs. Conclusion: In essence, the stakeholders involved in tourism development in the village have not applied an empowering approach for the community